KALIBRASI SENSOR ULTRASONIK HC-SR04 SEBAGAI SENSOR PENDETEKSI JARAK PADA PROTOTIPE SISTEM PERINGATAN DINI BENCANA BANJIR - Martalia Andayani; Widyaningrum Indrasari; Bambang. H. Iswanto (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
The water level detection sensor is a major component on flood early warning system. HC-SR04 Ultrasonic Sensor is usually used as a proximity sensor in a flood early warning system. The accuracy of the sensor is essential to support the effectiveness of a system. In this research, the calibration of HC-SR04 ultrasonic sensor using arduino microcontroller, which is it will be used on the prototype early warning system for floods. Calibration is done by taking reference to the warning status I, II, III, and IV of the Katulampa dam. The results showed that both sensor calibration can work well in the range of 14-250 cm, with a maximum relative error of 4.3%. The smallest change in distance that can be detected by the sensor by 1 cm with a maximum relative error of 0.91%. With the errors obtained, it can be said that the sensor is fit as a detector of the water level in flood early warning system prototype in 1:5 scale. Keywords: Ultrasonic Sensor, Arduino, Warning Status.